2014
DOI: 10.1093/rheumatology/keu022
|View full text |Cite
|
Sign up to set email alerts
|

Clinical usefulness of measuring red blood cell distribution width in patients with systemic sclerosis

Abstract: RDW in SSc may represent an integrative measure of multiple pathological processes including extensive vasculopathy, fibrosis or ongoing inflammation. An increase in RDW may indicate an impairment of cardiorespiratory function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 19 publications
2
31
0
Order By: Relevance
“…Lippi et al demonstrated a strong, graded association of RDW with ESR and CRP in a large cohort of unselected outpatients [8]. In addition, RDW has also been correlated with disease activity or acute-phase reactants in several chronic inflammatory conditions such as inflammatory bowel disease, Behcet's disease, RA, and scleroderma [9][10][11][12][13]20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lippi et al demonstrated a strong, graded association of RDW with ESR and CRP in a large cohort of unselected outpatients [8]. In addition, RDW has also been correlated with disease activity or acute-phase reactants in several chronic inflammatory conditions such as inflammatory bowel disease, Behcet's disease, RA, and scleroderma [9][10][11][12][13]20].…”
Section: Discussionmentioning
confidence: 99%
“…The apparent association between RDW and inflammation is strengthened by multiple studies demonstrating that RDW levels correlate with inflammatory markers and disease activity in several chronic inflammatory diseases [8][9][10][11][12][13]20].…”
Section: Introductionmentioning
confidence: 99%
“…In another study by Hassan et al [16], RDW level was found to be a useful parameter to show inflammation and high risk of progress. A high level of RDW also had a strong and independent correlation with ESR and CRP in systemic lupus erythematosis [17,18], Sjögren syndrome [19], systemic sclerosis [20], and familial mediterranean fever [21] patients in recent studies. RDW has also been found to be related to cardiovascular disease in various diseases [22].…”
Section: Discussionmentioning
confidence: 99%
“…Markers of inflammation such as increased CRP and ESR level, which may signify increased disease activity and unfavorable prognosis. Several studies showed that the level of ESR was significantly higher in patients with diffuse SSc than in those with localized SSc 7,8 .…”
Section: Introductionmentioning
confidence: 99%